Novel Approach of Linear Accelerator-Based Stereotactic Radiosurgery in an Adult Patient With Brain Arteriovenous Malformation: A Case Report and Clinical Outcome - Devarakonda, Santosh; Kontham, Vijay Kumar (International Clinical Neuroscience Journal, 2020)
Stereotactic radiosurgery (SRS) is a proven strategy for treating the central nervous system arteriovenous malformation (AVM). We intend to present a case of cerebral AVM in an adult patient, successfully treated with a linear accelerator (LINAC) based SRS using simplified setup techniques and an advanced planning system. In the current scenario, frame-based SRS is the standard of care with LINAC. Recently, it has proven that even frameless SRS has similar results. In our case, we used a frameless SRS technique with similar results. While calculating the dose in radiotherapy planning, we used the Acuros™ algorithm, which has proven dosimetric advantages compared to the traditional AAA™ algorithm.